Ética e direitos dos animais: a questão do especismo e do antiespecismo na filosofia política contemporânea - Oliveira, Hélio Rosa de (2022)
Analysis of the debate on the issue of animal rights in three dialoguing philosophical perspectives: speciesism, anti-speciesism and non-speciesism. The objective is to analyze each of these aspects, without the intention of exhausting any of them, from three paradigmatic thinkers: Carl Cohen, Tom Regan and Peter Singer. The investigation is developed taking as an entry point for the debate the proposal of Carl Cohen who denies that animals have rights, but defends that humans have responsibilities towards animals. Next, Tom Regan's conception as a litigant to the previous one is presented, since he not only criticizes Carl Cohen's speciesism but also states that non-human animals are beings that have rights by sharing gender properties, among which, to be able to feel pain and have emotions like humans. Finally, the ideas of non-speciesism are presented through Peter Singer's thinking, both in terms of the thesis of the moral necessity of guaranteeing rights to animals, and of basing human and animal relationships on practical ethics. This is done not only because of the philosophical dialogue between these authors regarding the object (animals have or do not have rights), but also because of the philosophical adherence to utilitarianism, although each one has a different conception of what is meant by “very common". It is believed that Peter Singer's perspective is the one that best meets the expectations of contemporary society, which not only have to balance ingrained habits (such as a meat-based diet and scientific experiments using animals) with the political demands of new social agents (including veganism), in terms of thinking about the new interfaces of modern law, including the possibility of including animals in this debate. Finally, it is argued that from the path proposed by Peter Singer it is possible to keep the dialogue open, think about the exceptions that the issue demands and carry out the project of including the issue of animal rights in the contemporary philosophical debate.